Dissociable hormonal profiles for psychopathology and stress in anorexia and bulimia nervosa. Issue 16 (28th December 2021) - Westwater, Margaret L.; Mancini, Flavia; Shapleske, Jane; Serfontein, Jaco; Ernst, Monique; Ziauddeen, Hisham; Fletcher, Paul C.
Abstract: Background: Anorexia nervosa (AN) and bulimia nervosa (BN) are complex psychiatric conditions, in which both psychological and metabolic factors have been implicated. Critically, the experience of stress can precipitate loss-of-control eating in both conditions, suggesting an interplay between mental state and metabolic signaling. However, associations between psychological states, symptoms and metabolic processes in AN and BN have not been examined. Methods: Eighty-five women ( n = 22 AN binge/purge subtype, n = 33 BN, n = 30 controls) underwent remote salivary cortisol sampling and a 2-day, inpatient study session to examine the effect of stress on cortisol, gut hormones [acyl-ghrelin, peptide tyrosine tyrosine (PYY) and glucagon-like peptide-1] and food consumption. Participants were randomized to either an acute stress induction or control task on each day, and plasma hormones were serially measured before a naturalistic, ad libitum meal. Results: Cortisol-awakening response was augmented in AN but not in BN relative to controls, with body mass index explaining the most variance in post-awakening cortisol (36%). Acute stress increased acyl-ghrelin and PYY in AN compared to controls; however, stress did not alter gut hormone profiles in BN. Instead, a group-by-stress interaction showed nominally reduced cortisol reactivity in BN, but not in AN, compared to controls. Ad libitum consumption was lower in both patient groups and unaffected by stress. Conclusions: Findings extend previous reports of metabolic dysfunction in binge-eating disorders, identifying unique associations across disorders and under stress. Moreover, we observed disrupted homeostatic signaling in AN following psychological stress, which may explain, in part, the maintenance of dysregulated eating in this serious illness.